The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.4064/bc118-12
|View full text |Cite
|
Sign up to set email alerts
|

Which sets are sets of lengths in all numerical monoids?

Abstract: We explicitly determine those sets of nonnegative integers which occur as sets of lengths in all numerical monoids.Dedicated to Jerzy Kaczorowski on the occasion of his 60th birthday.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Before finding sets of lengths which are characteristic for a given group, we determine those sets of non-negative integers which are sets of lengths over all finite groups. It turns out that this is a simple consequence of the associated result in the abelian setting (sets which are sets of lengths in all numerical monoids are determined in [22]).…”
Section: Arithmetic Of the Monoid Of Product-one Sequencesmentioning
confidence: 87%
“…Before finding sets of lengths which are characteristic for a given group, we determine those sets of non-negative integers which are sets of lengths over all finite groups. It turns out that this is a simple consequence of the associated result in the abelian setting (sets which are sets of lengths in all numerical monoids are determined in [22]).…”
Section: Arithmetic Of the Monoid Of Product-one Sequencesmentioning
confidence: 87%
“…Geroldinger and Schmid [31] investigated the intersection of systems of sets of lengths of numerical monoids. In particular, they proved ∩ L(M) = {{0}, {1}, {2}}, where the intersection is taken over all numerical monoids M = N. Gotti [36,Corollary 5.7] showed that if we take the previous intersection over all nontrivial atomic Puiseux monoids then we obtain ∩ L(M) = {{0}, {1}}.…”
Section: Sets Of Lengths and Their Unionsmentioning
confidence: 99%